Local religiosity and indigenous devotion in the Bourbon cycle: Archbishopric of La Plata, 1750-1808 - Castro Flores, Nelson (2013)
In this article we analyse the battering experimented by the local religiousness and the indigenous devotions, promoted by civil and ecclesiastic public servants on the second half of the XVIII century. We held the need to distinguish the public policies of the pastoral orientations, since the first one are linked to the need of control of the clergy and the reduction of the tax expenditure, which were translated in a trend to favour the fiscal and tributary tax obligations of the natives over the ones concerning devotion. In case of the pastoral rientations, these ones questioned the modalities that the local religiousness had assumed, subordinating them to lean on the universal church, and the indigenous devotions that were considered dominated by superstitions and excesses that were opposed to straight devotion and piety. These were faced from strategies of resymbolization that emphasized the intimist character and personal devotion, removed from the baroque theatricality and from the community frame.